Study on Vibration Characteristics of Vehicles Based on Non-linear Model of Air Spring - FANG Song; GAO Hongxing; CHI Maoru (机车电传动)
Based on the thermal-mechanics model and the non-linear ADAMS air spring model, the control models of air spring suspension system were established. By using the co-simulation platform of the multi-body dynamics simulation software SIMPACK and MATLAB/SIMULINK, the vehicle multi-body dynamics model including the above-mentioned control models was established, and the vehicle vibration characteristics under different non-linear models and different physical parameters of air spring were studied. Analysis results showed that: the thermal-mechanics model could accurately simulate the non-linear dynamic characteristics of air spring; the orifices of small diameter could improve vehicle vertical running stability when running at low speed; too large or too small diameters were not conducive to improve vehicle vertical running stability during high-speed running; the auxiliary reservoirs of larger volume were help to the improvement of vehicle vertical running stability, but when the volume increased to a certain degree , the improvement was not very obvious.